Passiflora zapalinamensis, a new species of supersect. Bryonioides (Passifloraceae) from northeast Mexico - Kuethe, J.r.; Encina-Domínguez, Juan A.; Cruz-Anaya, Arturo (Phytotaxa, 2022)
Passiflora zapalinamensis, a new species of the northern Mexican flora with uncinate trichomes, is herein described and illustrated. This species is endemic to the canyons and hills of the Sierra de Zapalinamé within the state of Coahuila, and the extended Sierra Madre Oriental of northeastern Mexico. It belongs to the subgenus Decaloba, supersection Bryonioides. It can be readily distinguished from its most morphologically similar species Passiflora hispidula by its subopposite to alternate glabrous nectaries, consistently rounded foliar apices, red stems and secluded distribution. Its taxonomy, ecology and conservation are discussed.